Pelatihan Singkat Servis Motor Bagi Siswa SMA Islam As Saadah Setu Tangerang Selatan - Bambang Herlambang; Budi Kaliwanto (Jurnal Kabar Masyarakat, 2024)
Motorized vehicles, especially motorbikes, have now become daily necessities, no longer classified as luxury goods. Due to the high level of need, almost every family has one motorbike, maybe even more than one. Motor vehicles are simple forms of transportation, can be driven in residential areas, both urban and rural, and the operational costs are relatively affordable for most groups. Current developments in motorbike design allow riders from young to old. Data shows that demand and use of motorbikes continues to increase. According to the Central Statistics Agency (BPS), in 2022 the number of vehicles in Indonesia will reach 148,212,865. The number of private vehicles in Indonesia is still dominated by motorbikes with a figure of 125,267,349 units (almost 85% of which are dominated by motorbikes). With the rapid increase in the number of motorized vehicles, many workshops and repairs have emerged, both large and small, official and unofficial workshops. The problems that arise are due to busyness, laziness or lack of knowledge and skills, so motorbike servicing is carried out at a repair shop. Especially for young people and students, who only like riding motorbikes, don't care about the condition of the motorbike, and don't learn how to service it even to repair minor damage. This will benefit the workshop. In fact, you should be able to save money if you can repair it yourself. It can even be detrimental if it is serviced by an irresponsible illegal workshop. From the results of surveys and observations at the Assa'adah Islamic Boarding School, South Tangerang, almost all students are unable to service their motorbikes themselves. Therefore, the team of Mechanical Engineering Lecturers at Pamulang University offers motorbike service training for students with the aim of giving them knowledge and skills in servicing motorbikes. Armed with this knowledge and skills, it is hoped that motorbike maintenance and if damage occurs, you can do it yourself, you don't need to take it to a repair shop. At least with this knowledge and skills, you can save financial expenses, and even the knowledge and skills obtained can become provisions for opening a motorbike service business in the future. The training offered is packaged in the form of Community Service (PKM) as one of the elements of the Tridharma of Higher Education. A short training method will be given in theory about motorbike service and maintenance, and practical motorbike service and maintenance will be carried out.